1998
DOI: 10.1021/ja980104y
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Induced Changes in the Electronic Structures of Some Flexible Benzenes. A Molecular Orbital Model

Abstract: High-resolution electronic spectroscopy experiments on several substituted benzenes in the gas phase have revealed a remarkable sensitivity of the orientation of the S 1 -S 0 transition moment (TM) in the molecular frame to the conformation of the attached group. Here, we explore the origins of this effect by performing ab initio calculations on five conformationally flexible benzenes (toluene, ethylbenzene, n-propylbenzene, 2-phenethyl alcohol, and 3-phenylpropionic acid) using the configuration interaction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 29 publications
4
54
0
Order By: Relevance
“…The relative energy of the A state is the negative of V dd , and therefore V dd is half the exciton splitting ͑this form is similar to that originally derived by McClure 2 except for the small contribution from the fourth-order term which was ignored there͒. 40 As a result, the increasing head-to- tail alignment with increasing for the antisymmetric TDM combination is the principal reason why the B state moves to lower energy in Fig. ͑4a͒-͑4c͒ into Eq.…”
Section: Dipole Model Predictions Of the Exciton Splittingsupporting
confidence: 59%
“…The relative energy of the A state is the negative of V dd , and therefore V dd is half the exciton splitting ͑this form is similar to that originally derived by McClure 2 except for the small contribution from the fourth-order term which was ignored there͒. 40 As a result, the increasing head-to- tail alignment with increasing for the antisymmetric TDM combination is the principal reason why the B state moves to lower energy in Fig. ͑4a͒-͑4c͒ into Eq.…”
Section: Dipole Model Predictions Of the Exciton Splittingsupporting
confidence: 59%
“…17 Theoretical studies using the ab initio CIS (6-31G*) method revealed that the effect is due to different degrees of perturbations of the unoccupied benzene * molecular orbitals by the side chain. 18 The perturbations produce a mixing of the low-lying * orbitals which are responsible for optical transitions to the S 1 and S 2 states. Further, single rovibronic linewidth measurements of the origin bands in the S 1 ←S 0 fluorescence excitation spectra of two conformers of n-propylbenzene show that the homogeneous bandwidth of the gauche conformer ͑65 MHz͒ is larger than the trans conformer ͑50 MHz͒.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting in passing that the fluorescence quantum yield of S 1 toluene has been observed to be temperature dependent, 29 and that the S 1 and S 2 excited states are believed to be mixed as a consequence of toluene adopting a quinoidal structure in S 1 . 30 Because the observed dynamics are occurring out of S 1 ͑v =0͒, IVR cannot be responsible, and this suggests that either intersystem crossing or internal conversion may be occurring, with the spectrum of the resulting T 1 or S 0 state contributing to the observed result, see later. However, even when overlapped 1 ps laser pulses are used to excite and ionize the sample, the ambient and jetcooled photoelectron spectra of S 1 ͑v =0͒ look noticeably different, although the congestion is significantly less pronounced, see Fig.…”
Section: Temperature Dependencementioning
confidence: 97%